Синтез (1,1-діоксидо-3-оксоізотіазолідин-2-іл)бензенамідів - Синюгін, А.Р.; Чеканов, М.О.; Лукашов, С.С.; Ярмолюк, С.М. (Інститут молекулярної біології і генетики НАН України, 2008)
Уперше синтезовано (1,1-діоксидо-3-оксоізотіазолідин-2-іл)бензоїлхлориди, на основі яких одержано ряд нових (1,1-діоксидо-3-оксоізотіазолідин-2-іл)бензамідів. Early it was shown some pharmacological value of substituted isothiazolin-3-one-1,1-dioxides. In our preliminary work the synthesis of isothiazolidin-3-one-1,1-dioxides was described. With the aim of widening of the range of isothiazolidinone-1,1-dioxide derivatives synthetic scheme of (oxoisothiazolidin-3-one-1,1-dioxide-2-yl) benzamides preparation was developed.